Effect of different extraction conditions on the production of anthraquinone - Nurul Ain, Jumri (2018)
Natural products have been used for generations and recently, the scientists have begun to show interest in Morinda citrifolia and its products. Its benefits become known where the roots of these plants were reported to be a good source of important compounds, called anthraquinones. Anthraquinone are widely acquired in nature to produce yellow or red dyes. However, the actual technical extraction and dyeing method of anthraquinone dyes are still unexplored. Morever, the natural dyes are often having low exhaustion color and poor fastness properties as its color is usually removed from the fibre during washing. This research was carried out to study the effects of types of solvent (ethanol, acetone, acetonitrile), solid liquid ratio (SLR) (1:100 to 5:100), extraction time (1 to 10 hour) and pH (1 to 11) on the concentration of anthraquinone using solvent extraction method. The solvent extraction method are found as a simplest extraction method which are also can improved color yield and the fastness properties of the fibres. The best condition of anthraquinone extract was determined using Response Surface Methodology (RSM). The anthraquinone extract was analysed and characterized using UV-Vis Spectrophotometer and Fourier Transform Infrared Spectroscopy (FTIR) respectively. The adsorption study was then conducted as three different factors, namely, the rate of adsorption on fibre using various initial dye concentrations (0.105 to 0.117 g/L), the effectiveness of adsorption on different types of fibre (spun silk, polyester spun silk and polyester cotton) and the duration of time (15 to 120 minutes) required for the process of adsorption on the fibre. The highest concentration of anthraquinone can be obtained by using acetone at the ratio of 4:100, 2 hours, and pH 7 of SLR, extraction times, and pH, respectively. However, the best condition for anthraquinone extraction using RSM for SLR and extraction times was 4:100 and 1 hour 30 minutes respectively. Production of anthraquinone in this study increased about 66.67 % as; 0.003 g/g (0.102 g/L) compared to previous study; 0.001 g/g of anthraquinone production yield (Vázquez et al., 2014). This comparison proved the solvent extraction used in this study was applicable for further study. In fact, Vázquez et al. (2014) use two types of solvents; benzene and ethyl acetate, and require longer extraction time (16 hours). The different anthraquinone yield might be because of different types of raw material, extraction method and solvent used. The equilibrium time and initial dye concentration fitted for adsorption process of anthraquinone was determined to be 60 minutes and 0.117 g/L, respectively. Spun silk fibre was found has the highest adsorption effectiveness, followed by polyester spun silk and polyester cotton fibre. The order of isotherm equations followed by the present data is Langmuir > Freundlich isotherm. As for conclusion, the study suggested that the roots of Morinda citrifolia can yield a reddish brown colour that has potential in the textile industries since the best conditions of dyeing process of anthraquinone dye were determined. Anthraquinone served as an eco-friendly alternative to their synthetic equivalents to make a greener life. The anthraquinone extracted in this study give a high value product to the textile industry like ‘Tenun Diraja Pahang’ for commercialization.